The Connectedness of the Coronavirus Disease Pandemic in the World: A Study Based on Complex Network Analysis - Zhu, Sha; Kou, Meng; Lai, Fujun; Feng, Qingxiang; Du, Guorong (Frontiers in Physics, 2021)
Since the coronavirus disease (COVID-19) pandemic started at the beginning of 2020, it has seriously affected various countries' economic and social development and accelerated the economic recession worldwide. Therefore, the connectedness of the global COVID-19 network across countries is studied in this paper. Based on the COVID-19 correlations in 122 countries, this paper constructed a complex network of the COVID-19 from January 19, 2020, to August 15, 2020. Our paper then deconstructs the overall global network connectedness and analyzes the connectedness characteristics. Moreover, we empirically investigate the network connectedness influencing factors by using various countries' macroeconomic and social data. Our paper finds that the global COVID-19 pandemic network has some prominent complex network properties, such as low length, high clustering, and good community structure. Furthermore, population density, economic size, trade, government spending, and medical treatment are significantly macro factors affecting the COVID-19 connectedness in different countries.